Efficacy and safety of perioperative sintilimab plus platinum-based chemotherapy for potentially resectable stage IIIB non-small cell lung cancer (periSCOPE): an open-label, single-arm, phase II trialResearch in context - Xiangyang Yu; Chujian Huang; Longde Du; Chunguang Wang; Yikun Yang; Xin Yu; Shengcheng Lin; Chenglin Yang; Hongbo Zhao; Songhua Cai; Zhe Wang; Lixu Wang; et al. (EClinicalMedicine)
Summary: Background: The absolute overall survival (OS) improvement with preoperative chemotherapy or chemoradiotherapy in locally advanced non-small cell lung cancer (NSCLC) patients is controversial and unsatisfactory. We designed this trial to explore the efficacy and safety of perioperative sintilimab plus platinum-based chemotherapy for potentially resectable stage IIIB NSCLC to facilitate further optimization of this therapeutic strategy. Methods: Patients diagnosed with stage IIIB NSCLC through invasive staging approaches and/or PET/CT scans and evaluated as having a high probability of radical resection of the primary lesion and metastatic lymph nodes with clear pathological margins by a multidisciplinary team were enrolled in this open-label, single-arm, phase II trial at a single centre in China. The participants received two cycles of intravenous neoadjuvant treatment with PD-1 inhibitor sintilimab (200 mg), pemetrexed (500 mg/m2) for adenocarcinoma, paclitaxel (175 mg/m2) or nab-paclitaxel (260 mg/m2) for other histological subtypes, plus carboplatin (area under the curve 5) or cisplatin (75 mg/m2) on the first day of each 3-week cycle. Surgical resection was performed 28–42 days later. After recovery from surgery, two cycles of adjuvant treatment were carried out in strict conformity with the neoadjuvant regimen, and then sintilimab maintenance monotherapy were given. The primary endpoint was major pathological response (MPR). The key secondary endpoints included the objective response rate (ORR), radical resection (R0) rate, pathological complete response (pCR) rate, event-free survival (EFS), disease-free survival (DFS), OS, treatment-related adverse events (TRAEs), surgical complications, and surgery delay rate. This trial is registered with the Chinese Clinical Trial Registry (ChiCTR2000040673). Findings: Forty-one patients were assessed for eligibility between December 2020 and August 2022; 30 patients were enrolled and given two cycles of neoadjuvant chemoimmunotherapy (neoCIT). Nineteen patients achieved a radiographic partial response, resulting in an ORR of 63.3%. Although 26 patients (86.7%) experienced TRAEs during the neoadjuvant phase, only two patients (6.7%) had ≥ grade 3 TRAEs. Surgical resection was performed on 27 patients (90%), with two patients experienced surgical delay because of coronavirus disease 2019, and the R0 rate was 96.4%. Twelve patients (44.4%) in the per-protocol (PP) population achieved an MPR, including six patients (22.2%) with a pCR. The most common postoperative complications were atrial fibrillation (6, 22.2%), pneumonitis (5, 18.5%), and heart failure (4, 14.8%); no deaths occurred within 90 days after surgery. As of October 31, 2024, the median follow-up was 34.7 months. The estimated EFS and OS rates at 36 months in the intention-to-treat population were 42.8% and 70.1%, respectively, and the estimated DFS and OS rates at 36 months in the PP population were 52.5% and 70.4%, respectively. Interpretation: Perioperative sintilimab plus platinum-based chemotherapy is an emerging treatment option for patients with potentially resectable stage IIIB NSCLC; it has a high response rate and tolerable treatment-related toxic effects, and enables radical resection in most patients. Funding: The Cancer Research Program of National Cancer Center (NCC201919B02), Shenzhen Clinical Research Center for Cancer (No. [2021]287), Shenzhen High-level Hospital Construction Fund, Shenzhen Key Medical Discipline Construction Fund (SZXK075) and Sanming Project of Medicine in Shenzhen (SZSM201612097) funded this study.